Os Estados Unidos e a Operação Condor - Dalenogare Neto, Waldemar (2020)
This doctoral thesis discusses the United States participation in Operation Condor through the analysis of documents released by the U.S State Department and the Central Intelligence Agency (CIA). I analyze the post-World War II context and the era of counterinsurgency in American intelligence, which would be echoed in U.S foreign policy towards the southern cone during the Nixon/Ford administration through Secretary of State Henry Kissinger and his realpolitik. The United States knew the existence of Operation Condor, provided logistical support for the implementation of the communication system - CONDORTEL - and recorded the steps of this repressive structure. There was never, however, a disapproval note - and the only U.S State Department proposal for a démarche on the subject was abandoned in 1976. With Jimmy Carter and his human rights foreign policy, in the first year of his term there was a strong diplomatic pressure directed towards the southern cone countries. Along with the restructuring of the CIA, which changed its method to signal intelligence, and also the attempt to break with Kissinger's geopolitical order in State Departament, Carter received harsh criticism for breaking relations with the traditional southern cone partners. The Letelier case, the threats registered by the CIA and the internal developments of Condor - such as Operation Teseo, are also discusses. In 1978, however, there was a shift in Carter's foreign policy, deepened by the subsequent crises in Iran and Afghanistan, which would put foreign human rights policy in the background. Condor, slowly, would take its repressive structure to Central America, in Operation Charly.